Tackling Health Care Disparities: How to Build a Sarcoidosis Center - Kron, Jordana; Syed, Aamer; Iden, Thomas; Gwathmey, Kelly; Polly, Kelly; Randolph, Jessica; Brar, Vikram; Nana-Sinkam, Patrick; Ellenbogen, Kenneth; Syed, Huzaefah (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Sarcoidosis is a multi-organ system inflammatory disease of unknown etiology that disproportionately affects women and black patients in the United States. In addition, woman and minority patients have worse outcomes. In 2015, sarcoidosis physicians in cardiology, pulmonary medicine and rheumatology joined forces to create a multidisciplinary sarcoidosis at Virginia Commonwealth University. In 2019, the clinic was recognized as a World Association of Sarcoidosis and Other Granulomatous Disorders (WASOG) Center of Excellence. We identify four pillars of a patient-centered sarcoidosis clinic: clinical care, research, teaching, and community outreach. We detail how each of these facets plays a critical role in improving the health of individual patients, creating a strong infrastructure to improve the future of sarcoidosis treatment, and developing community-based resources that can empower patients. Most importantly, we highlight how a multidisciplinary clinic can help identify and combat healthcare disparities.